Radioiodine adjuvant therapy in differentiated thyroid cancer: An update and reconsideration - Sun, Yu-qing; Sun, Di; Zhang, Xin; Zhang, Ying-qiang; Lin, Yan-song (Frontiers in Endocrinology, 2022)
Radioiodine (131I) therapy (RAI) has been utilized for treating differentiated thyroid cancer (DTC) for decades, and its uses can be characterized as remnant ablation, adjuvant therapy (RAT) or treatment for known diseases. Compared with the definite 131I treatment targets for remnant ablation and known disease, 131I adjuvant therapy (RAT) aims to reduce the risk of recurrence by destroying potential subclinical disease. Since it is merely given as a risk with no imaging confirmation of persistence/recurrence/metastases, the evidence is uncertain. With limited knowledge and substance, the indication for RAT remains poorly defined for everyday clinical practice, and the benefits of RAT remain controversial. This ambiguity results in a puzzle for clinicians seeking clarity on whether patients should receive RAT, and whether patients are at risk of recurrence/death from undertreatment or adverse events from overtreatment. Herein, we clarified the RAT indications in terms of clinicopathological features, postoperative disease status and response to therapy evaluation, and retrospectively examined the clinical outcomes of RAT as reported in current studies and guidelines. Furthermore, given the evolution of nuclear medicine imaging techniques, it can be expected that the future of RAT may be advanced by nuclear medicine theranostics (i.e., 131I whole-body scan, PET/CT) by accurately revealing the biological behaviors, as well as the underlying molecular background.